PENGARUH DANA ALOKASI UMUM TERHADAP TINGKAT KEMANDIRIAN KEUANGAN DAERAH, TAX EFFORT (UPAYA PAJAK), DAN ALOKASI BELANJA MODAL DI JAWA TIMUR - VIRGI ARDHANI, SEPTYAS Virgi (Jurnal Akuntansi AKUNESA, 2014)
The purpose of this research is to examine the impact of General Allocation Fund toward Regional Financial Independence, Local Tax Effort in district/city, and capital expenditure at East Java Province. General Allocation Fund is proportion fund from central governance to smooth the district’s finance capability. This research use simple linier regression into three models. Dependent variables are Regional Financial Independence, Local Tax Effort, and capital expenditure, the independent variable is General Allocation Fund. The result of this research are General Allocation Fund has a negative impact to the Regional Financial Independence and also General Allocation Fund has negative impact to the local tax effort. Then, General Allocation Fund has no impact to the capital expenditure. Keyword: General Allocation Fund, Regional Financial Independence, Local Tax Effort, and capital expenditure